Challenges to implementing of development plans at local-level government in Papua New Guinea (Commonwealth Journal of Local Governance, 2015)
The 1995 local-level government reforms undertaken in Papua New Guinea (PNG) were largely in response to increasing concern that the public service was failing in its responsibility towards the people.  As a result, the 1995 Organic Law on Provincial and Local Governments (OLPLLG) was established.  The prime purpose of this was to address this issue through deeper engagement of the lower levels of government, particularly local-level governments (LLGs). Almost two decades on, poor socio-economic conditions and deterioration in infrastructure/services suggest that the proposed change has not materialised.  The purpose of this paper is to address the question of whether the lower tiers of government are capable of implementing the development plans under the reforms.  The paper finds that the 1995 reforms have made LLGs dependent upon their Joint District Planning and Budget Priorities Committee (JDP & BPC) and their district administration, which have become the main impediment to local government effectiveness.  This in turn has greatly hindered LLG capacity and has reinforced unequal relations, rather than assisting service delivery in PNG.  There is therefore a need to make LLGs more effective players.